ANALISIS KONSENTRASI LOGAM TIMBAL (Pb) PADA IKAN GULAMA (Sciaena russelli) DI KAWASAN PERAIRAN LAUT DUMAI SEBAGAI RANCANGAN POSTER PEMBELAJARAN BIOLOGI SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Dumai sea waters have various port activities, industry, transportation, aquaculture and domestic activities that produce heavy metal Pb. The increase in metal concentration in the waters will accumulate in the Gulama fish (Sciaena russelli). This study aims to determine the concentration of heavy metal lead (Pb) contained in Sciaena russelli in the Dumai marine area and used as a learning media design in the form of posters. This research was conducted by survey method with purposive random sampling in determining the sampling location. The results showed that the concentration of heavy metal Pb in the Dumai marine waters ranged from 0.0077-0.0256 with the highest concentration at the port and the lowest concentration in domestic activities. The concentration of heavy metal Pb showed an increase in the accumulation in marine waters and fish tissue of Sciaena russelli in the range of 0.0311-0.0605. The highest concentration is at the port and the lowest is at the station without settlement. The results of the study can be used as one of the learning media in the form of posters on environmental pollution material for class X SMA.Key Words: Lead Heavy Metal, Dumai sea pollution, Sciaena russelli